2007
DOI: 10.1161/hypertensionaha.107.090084
|View full text |Cite
|
Sign up to set email alerts
|

Awake Systolic Blood Pressure Variability Correlates With Target-Organ Damage in Hypertensive Subjects

Abstract: Abstract-Growing evidence associates blood pressure (BP) variability with cardiovascular events in hypertensive patients. Here we tested the existence of a relationship between awake BP variability and target-organ damage in subjects referred for suspected hypertension. Systolic and diastolic BP variability were assessed as the standard deviation of the mean out of 24-hour, awake and asleep BP recordings in 180 untreated subjects, referred for suspected hypertension. Measurements were done at 15-minute interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
178
1
20

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 258 publications
(211 citation statements)
references
References 53 publications
12
178
1
20
Order By: Relevance
“…17 However, Tatasciore et al reported that nighttime systolic BPV was not correlated with target-organ damage in patients with untreated and recently diagnosed hypertension. 18 Similarly, in our study, nighttime BPV was not correlated with aortic size index, but 24-hour and daytime systolic BPV were found to be positively correlated with aortic size index in recently diagnosed hypertensive patients.…”
Section: Discussionsupporting
confidence: 67%
“…17 However, Tatasciore et al reported that nighttime systolic BPV was not correlated with target-organ damage in patients with untreated and recently diagnosed hypertension. 18 Similarly, in our study, nighttime BPV was not correlated with aortic size index, but 24-hour and daytime systolic BPV were found to be positively correlated with aortic size index in recently diagnosed hypertensive patients.…”
Section: Discussionsupporting
confidence: 67%
“…Based on 24h ambulatory BP measurements, several studies have reported that both visit-to-visit BPV and short-term BPV were correlated with AS [10][11][13][14][15]. BPV has been reported to be closely associated with CAS [13][14][15]20].…”
Section: Discussionmentioning
confidence: 99%
“…BPV has been reported to be closely associated with CAS [13][14][15]20]. However, due to the existence of various BPV indices and poor reproducibility of these indices, it is difficult to draw solid conclusions about the relationship between BPV and CAS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations